2016
DOI: 10.1111/aos.13330
|View full text |Cite
|
Sign up to set email alerts
|

New neovascular age‐related macular degeneration is associated with systemic leucocyte activity

Abstract: Systemic leucocyte activity is associated with onset of CNV in patients with AMD and correlate with lesion size and BCVA, which suggest that acute systemic immune activity may play a role in neovascular flaring of AMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…Some of these patients informed that they did not seek help after several months, which is particularly problematic since timely treatment can be important factor for neovascular AMD [39, 40]. It is hard to speculate whether these challenges reflect a generation issue in not wanting to burden others, cognitive decline that are seen in among the very old, or a concept of accepting that vision declines with age.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these patients informed that they did not seek help after several months, which is particularly problematic since timely treatment can be important factor for neovascular AMD [39, 40]. It is hard to speculate whether these challenges reflect a generation issue in not wanting to burden others, cognitive decline that are seen in among the very old, or a concept of accepting that vision declines with age.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid blurring the results from immunological co‐morbidities, we did not recruit individuals with known altered immune dysfunction (active cancer, autoimmune disease or any immune, infectious or inflammatory diseases, or patients who were receiving chemotherapy or any immune modulating therapy). Cases with a recent CNV onset were also not considered because of possible acute immune activity . Participants with elevated plasma C‐reactive protein (CRP) levels (>15 mg/L) were post hoc excluded as this is a sign of ongoing acute immune response .…”
Section: Methodsmentioning
confidence: 99%
“…Development of choroidal neovascularizations (CNVs) defines the late stage of neovascular age‐related macular degeneration (AMD). Monocytes play an important role as shown in several studies: tissue specimens of neovascular AMD show macrophages in significantly higher number around the lesion, experimental CNV in mice is attenuated in size upon experimental depletion of circulating monocytes, patients with new‐onset neovascular AMD have increased circulating monocytes and retinal injury leads to chemokine secretion to which circulating monocytes are drawn . These monocytes respond to the injury by secreting vascular endothelial growth factor (VEGF) .…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, intermediate monocytes are thought to be associated with antigen presentation. Some studies have suggested that the proportion of the three monocyte classes is unchanged in advanced AMD, although an increase in monocytes has been reported during the first month following the onset of neovascular AMD . However, changes gene expression (transcriptome) in monocytes isolated from subjects with neovascular AMD highlight that alterations occur in peripheral blood monocytes during disease.…”
Section: Peripheral Blood Monocytes and Age Related Macular Degenerationmentioning
confidence: 52%